Preparation and characterization of UV-curable epoxy/silica nanocomposite coatings - KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE SA, 2009)
To enhance the interfacial interaction in silica nanoparticles filled polymer composites, the silica surface was firstly treated with glycidoxypropyl trimethoxysilane (GPTMS), and its structure was analyzed by C-13 NMR and FTIR spectro photometry. Then a series of GPTMS-modified silica/cycloaliphatic epoxy nanocomposite coatings with 0-6 wt% silica content were prepared by UV-induced cationic polymerization in the presence of a diaryliodonium photoinitiator and thioxanthone photosensitizer. The physical and mechanical properties such as hardness, adhesion, gloss, impact as well as tensile strength were examined. As a result, these composites demonstrated superior tensile strength and tensile modulus with increasing proportion of modified silica LIP to a certain level. An increase in abrasion resistance of nanocomposites with the addition of modified silica was observed. The thermal stability of nanocomposites was not enhanced with the addition of silica particles. SEM studies indicate that silica particles were dispersed homogenously through the polymer matrix. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Silica particles; Cycloaliphatic epoxy; Cationic polymerization; UV-curing; Nanocomposite; SILICA; FILMS; SIZE